2015
DOI: 10.2220/biomedres.36.71
|View full text |Cite
|
Sign up to set email alerts
|

<b>1α,25(OH)</b><b><sub>2</sub></b><b>D</b><b><sub>3</sub></b><b> downregulates gene expression levels of muscle ubiquitin ligases MAFbx and MuRF1 in human </b><b>myotubes </b>

Abstract: Clinical trials involving in patients with osteoporosis have reported that activated vitamin D 3 (1α,25(OH) 2 D 3 , calcitriol) can prevent falling by acting on the skeletal muscles. However, pharmacological mechanisms of 1α,25(OH) 2 D 3 with respect to skeletal muscle hypertrophy or atrophy are still poorly understood. Therefore, we examined changes in the expression of several related genes in human myotubes to test whether 1α,25(OH) 2 D 3 influences hypertrophy and atrophy of skeletal muscle. Myotubes treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Decreases in Murf1 and Mafbx in mVDR mice would support better maintenance of fibre size with inhibition of the ubiquitin–proteosome pathway. Interestingly, these were also decreased in human myotubes treated with vitamin D, suggesting the possibility that in mVDR mice, the decrease could be mediated by effects of another cell type with intact vitamin D signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in Murf1 and Mafbx in mVDR mice would support better maintenance of fibre size with inhibition of the ubiquitin–proteosome pathway. Interestingly, these were also decreased in human myotubes treated with vitamin D, suggesting the possibility that in mVDR mice, the decrease could be mediated by effects of another cell type with intact vitamin D signalling.…”
Section: Discussionmentioning
confidence: 99%
“…MAFbx and MuRF1 mRNA levels were not significantly different between rat skeletal muscle with and without infusion of IL-6 [ 13 ]. Although MAFbx mRNA was increased by 100 ng/mL of IL-6 and MuRF1 mRNA was significantly increased by 10 and 100 ng/mL IL-6, MAFbx mRNA was not increased by 1 or 10 ng/mL of IL-6 and MuRF1 mRNA was not increased by 1 ng/mL of IL-6 in human myocytes [ 25 ]. In this study, LPS increased IL-6 levels by up to approximately 0.94 ng/mL, which may be too low to increase MAFbx and MuRF1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have previously shown that vitamin D represses atrogene expression [ 16 ]. However, we have demonstrated for the first time that vitamin D represses the expression of MuRF1 and atrogin-1 in a mouse model of disuse-induced atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH) 2 D 3 and other forms of vitamin D have been shown to repress IL-6 in vitro and in vivo [ 14 , 15 ]. One study has reported that 1,25(OH) 2 D 3 downregulated MuRF1 and atrogin-1 expression in human myotubes [ 16 ]. In this way, HMB and 1,25(OH) 2 D 3 have been supposed to possess both anti-atrophic effects and IL-6-repressing effects, but the relationship between these effects is unclear.…”
Section: Introductionmentioning
confidence: 99%